Regular narrow QRS tachycardia. What is the mechanism?. Issue 4 (8th March 2021) - Mohanan Nair, Krishna Kumar; Prabhu, Mukund Aravind; Balaguru, Sridhar; Namboodiri, Narayanan; Valaparambil, Ajitkumar
Abstract: A 45‐years‐old lady with no structural heart disease on echocardiogram presented with recurrent episodes of palpitation. There was no baseline preexcitation. Twelve lead surface electrocardiograms (ECG) recorded during one of the episodes are provided. What is the likely mechanism of the tachycardia?